Emansipasi Melawan Pandemi Global: Bukti Dari Indonesia - Titik Nurhayati; Rizqon Halal Syah Aji (ADALAH, 2020)
Abstract:Emancipation against COVID-19 is very urgent, especially in Indonesia. The vulnerability of the impact of the COVID-19 pandemic is more likely to be experienced by women. Women in various parts of the world continue to make efforts to emancipate against this pandemic. Do not miss in Indonesia, how the involvement of women's emancipation. The focus on creating affirmations for domestic and public economic resilience continues to be carried out entirely by women in the context of emancipation. The foundation of women's fiqh which makes the role of shar'i a foothold of emancipation in the domestic and public sphere. Confidence in making concrete steps to emancipation in an effort to strive for family economic resilience becomes clear.Keywords: Emancipation, COVID-19, economic resilience, working women, fiqh of women.Abstrak:Emansipasi dalam melawan COVID-19 sangat mendesak dilakukan, khususnya di Indonesia. Kerentanan dampak pandemi COVID-19 lebih cenderung dialami perempuan. Perempuan diberbagai penjuru dunia terus berupaya melakukan emansipasinya dalam melawan pendemi ini. Tidak ketinggalan di Indonesia, bagaimana keterlibatan emansipasi perempuan. Fokus menciptakan afirmasi untuk ketahanan ekonomi domestik maupun publik terus dilakukan sepenuhnya oleh perempuan dalam rangka emansipasi. Landasan fiqih perempuan yang menjadikan role syar’i menjadi pijakan emansipasi dalam ranah domestik maupun ranah publik. Keyakinan melakukan langkah kongkrit emansiapsi dalam upaya mengupayakan ketahanan ekonomi keluarga menjadi jelas.Kata Kunci: Emansipasi, COVID-19, Ketahanan Ekonomi, Perempuan Pekerja, Fiqih Perempuan